Suboptimal control for patients with type 2 diabetes in the Central Chronic Medicine Dispensing programme in South Africa - Patrick Ngassa Piotie; Elizabeth M. Webb; Paul Rheeder (AOSIS, 2021)
Background: In South Africa, the Central Chronic Medicine Dispensing and Distribution (CCMDD) programme allows stable patients with non-communicable diseases, including type 2 diabetes mellitus (T2DM), to collect their medication from a pick-up location near their home, thus avoiding long waiting times and travel expenses. The CCMDD programme aims at improving patient retention and adherence through better access to medicines, resulting in better health outcomes. Aim: We assessed whether patients with T2DM enrolled in CCMDD achieved the recommended targets for glycaemic, blood pressure (BP) and lipid control. Setting: City of Tshwane, South Africa. Methods: We reviewed the records of 198 T2DM patients enrolled in CCMDD and assessed their control of haemoglobin A1c (HbA1c), BP and lipids. Results: Most of the records reviewed belonged to women (64.7%), African (89.9%), hypertensive (82.7%) and to patients exclusively on oral antidiabetic agents (98.5%). Patients were, on average, 57.7 (s.d. = 12.1) years old and had participated in the CCMDD programme for, on average, 2 years. The mean HbA1c was 8% (s.d. = 2). Glycaemic control was achieved by only 29.2% of patients, and 49% of patients had HbA1c between 7% and 9%. Ninety-three patients (66%) had achieved the total cholesterol target, 57.4% achieved BP targets and 6.9% had achieved the low-density lipoprotein cholesterol target. Conclusion: A small group of patients achieved the targets for glycaemic, BP and lipid control. Despite improved accessibility to medication, the CCMDD is not synonymous of improved clinical outcomes. Future research should ascertain the factors associated with suboptimal control for these patients.